2021
DOI: 10.1007/s00428-021-03182-7
|View full text |Cite
|
Sign up to set email alerts
|

Papillary lesions of the breast

Abstract: Papillary lesions of the breast represent a heterogeneous group of lesions including benign papillomas, papillomas with focal epithelial atypia, fully fledged ductal carcinoma in situ (DCIS) or lobular neoplasia, papillary DCIS, encapsulated papillary carcinomas without or with invasion, solid papillary carcinomas, and invasive papillary carcinomas. A micropapillary pattern characterized by lack of fibrous stalks within the papillae is observed in micropapillary DCIS and invasive micropapillary carcinoma. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 84 publications
0
38
0
2
Order By: Relevance
“…Although IMPC was listed as a subtype of invasive breast carcinoma in 1993, no consensus has been successfully reached on which criteria to use for diagnosis and determining the type of disease based on the percentage of the IMPC component (12). Regardless of the tumor size and the proportion of the IMPC component, a few studies have emphasized the importance of the histologic features in determining the invasiveness of IMPC (4,13). In our study, data from 63 patients with a micropapillary component ratio ranging from 10% to 100% were reviewed, and the clinical imaging features were highly indicative of the malignancy of IMPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IMPC was listed as a subtype of invasive breast carcinoma in 1993, no consensus has been successfully reached on which criteria to use for diagnosis and determining the type of disease based on the percentage of the IMPC component (12). Regardless of the tumor size and the proportion of the IMPC component, a few studies have emphasized the importance of the histologic features in determining the invasiveness of IMPC (4,13). In our study, data from 63 patients with a micropapillary component ratio ranging from 10% to 100% were reviewed, and the clinical imaging features were highly indicative of the malignancy of IMPC.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen years later, IMPC was defined and included in the World Health Organization's (WHO) classification of breast tumors (3). Pathologists have described IMPC lesions as having an inside-out reversed polarity pattern with a typical cuticle-like microvillous secretory surface facing the stroma, resulting in a gap between the stroma and the neoplastic epithelial cells (4). Prior studies have demonstrated that as an aggressive variant, IMPC is linked to a larger tumor size, more advanced Tumor, Node, Metastasis (TNM) staging, a greater proportion of nodal involvement, and a higher degree of lymphovascular invasion (LVI); these characteristics can contribute to a high early recurrence rate and a poorer prognosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…IMPC is easy to early metastasized to lymph node is the most prominent characteristics, some patients before early diagnosis, cancer cells already metastasized throughout the body through the blood vessels, lymphatic system, the risks of recurrence of primary focal distance and metastasis of cancer cells were reduced [12] . As early as 2004, Pettinato et al reported that IMPC lymph node metastasis rate was as high as 80 % [13] .…”
Section: Discussmentioning
confidence: 99%
“…Fragments of a benign papilloma in a breast biopsy are considered a lesion of uncertain malignant potential (B3 in the European classification), and excision is mostly recommended [ 5 ], although its necessity has been subject to debate [ 6 8 ]. A single papilloma imparts a cancer risk similar to conventional proliferative fibrocystic change.…”
Section: Introductionmentioning
confidence: 99%